E-046 Thromboembolic and Haemorrhagic Complications Associated with Endovascular Coil Embolization of Ruptured Basilar Apex Aneurysms. (26th July 2014) - Ding, D; Raper, D; Starke, R; Hilliard, J; Evans, A; Jensen, M; Liu, K
Abstract : Introduction: The basilar apex is the most common posterior circulation location for aneurysmal subarachnoid haemorrhage (SAH). In the current era of intracranial aneurysm treatment, the vast majority of basilar apex aneurysms are being targeted with endovascular therapy. While the obliteration and retreatment rates of endovascular aneurysm occlusion have been extensively studied, the incidences of thromboembolic and haemorrhagic complications have not been analyzed in detail. We report our institutional neurointerventional experience with the treatment of ruptured basilar apex aneurysms which particular attention to periprocedural complications. Methods: We retrospectively reviewed a prospective, institutional review board approved database of patients with ruptured basilar apex aneurysms who were treated by endovascular therapy at the University of Virginia from 1999 to 2010. Patient demographics, aneurysm size, endovascular treatment approach, use of postprocedural anticoagulation, rate of periprocedural thromboembolic and haemorrhagic complications, and clinical outcomes were reported. The modified Rankin Scale (mRS) was used to classify clinical outcomes. Pearson's chi-squared test was used to compare the risk of thromboembolic versus haemorrhagic complications and the complication rates based on treatment approach and aneurysm size. Results: The median patient age was 54 years (range 36 to 87 years) and 68% were female. The median aneurysm size was 7 mm (range 3 to 22 mm). Four patients also had superior cerebellar artery aneurysms (7%) of median size 3 mm. The endovascular treatment approach was single microcatheter coil embolization in 74%, dual microcatheter coil embolization in 7%, balloon-assisted coil embolization in 2%, and stent-assisted coil embolization in 17%. Single or dual antiplatelet therapy was administered following endovascular treatment in 28% and 19% of patients, respectively. A postprocedural heparin infusion for 24 to 48 h was administered to 16% of patients due to intraprocedural thromboembolic complications. The rates of thromboembolic and haemorrhagic complications were 18% and 5%, respectively. One aneurysm was unable to be coiled (2%). The median mRS score was 3 for patients with complications including 2 for thromboembolic and 4.5 for haemorrhagic complications. Thromboembolic complications were significantly more common than haemorrhagic complications (P = 0.039). Complications tended to occur more frequently in aneurysms treated by single microcatheter coiling than in aneurysms treated by non-single microcatheter techniques (29% vs. 7%, P = 0.083). Aneurysms less than 7 mm in diameter had similar complication rates to aneurysms at least 7 mm in size (22% vs. 24%, P = 0.87). Conclusions: Patients treated by endovascular coil embolization for ruptured basilar apex aneurysms are significantly more likely to experience thromboembolic complications than haemorrhagic ones. There is a trend toward a higher complication risk with single microcatheter treatment compared to dual microcatheter, balloon-assisted, or stent-assisted coil embolization for these lesions. Future studies are needed to determine the safety and efficacy of more aggressive preprocedural and intraprocedural anticoagulation regimens for the endovascular treatment of basilar apex aneurysms in the setting of SAH. Disclosures: D. Ding: None. D. Raper: None. R. Starke: None. J. Hilliard: None. A. Evans: None. M. Jensen: None. K. Liu: None.